Elaboração e validação de um Instrumento de rastreio para o Transtorno Dismórfico Corporal - Cavalcanti, Alcira de Lourdes Teotonio (2018)
Body Dysmorphic Disorder (DBS), according to DSM-5, is a disorder in which individuals who suffer from it see body deformity in one or more parts of themselves. This disorder is characterized by Obsessive Compulsive Disorder (OCD), because of its comorbidities. The focus on a body anomaly is its diagnostic differential. However, BDD is underdiagnosed and thereby increases the intensity of symptoms that can lead individuals suffering from this disorder to commit suicide. Considering the need for an early evaluation of this disorder, this study aimed to elaborate and obtain evidence of validity and reliability of the Body Dysmorphic Disorder Screening Instrument (IRTDC). For this, initially, the research was presented to the Research Ethics Committee, receiving approval for execution in protocol n ° 2,089,447. The study was divided into three stages, namely: (1) elaboration of 80 items for the IRTDC, in addition to semantic and judges analysis; (2) pilot study with sample (convenience) of 169 university students; and (3) final study with a sample of 612 subjects divided into 3 groups (university students, high school students and clinical subjects). In the first step there were no changes to the items of the instrument. However, after the psychometric analysis (Principal Components Analysis and Item Response Theory), in the pilotstudy, there were 47 items whose psychometric coefficients were not adequate. In addition, the unidimensionality of the instrument was verified. In the final study, the instrument underwent Exploratory Factor Analysis (AFE), Confirmatory (AFC) and item analysis through Item Response Theory (TRI), in addition to obtaining evidence of criterion validity. Other analyzes of group comparison were performed, in addition to correlation and regression analyzes. It was concluded that the instrument is valid in exploratory and confirmatory factorial terms (GFI = 0.999, AGFI = 0.999, TLI = 0.992, CFI = 0.993, PGFI = 0.846, RMSEA = 0.080) and reliable (Alpha = 0.965). The items of the instrument also presented good parameters of difficulty and discrimination according to TRI. Furthermore, the instrument presented evidence of validity of external criteria, since it was able to differentiate the subjects from the clinical group, with higher average scores (87.05) from university groups (56.95) and high school students (73.09). In addition, we also found evidence that the IRTDC was able to differentiate the scores of men and women, both in the general group and in the clinical group, in which the men scored less and more respectively. Finally, we found results that allow us to affirm that age predicts BDD in a negative way, that is, the lower the age, the higher the score in the BDET, explaining 21.4% of the prediction for the construct. It was concluded that the IRTDC presented evidence of validity and reliability for use in research.